Democracy, Identity, and Foreign Policy in Turkey Hegemony through Transformation - Keyman, E. Fuat.; Gumuscu, Sebnem; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Through critical analysis of Turkey's transformation under the AKP, this book explores the relationship between domestic transformations and global/regional dynamics. It also discusses the relationship between the Turkish transformation and the Arab uprisings and the implications of the Turkish case for regime transitions in the Arab world.
Keywords: Science; Science; Science, general